Microbiology of slipper-shaped oysters sold in some wet markets of NCR, Philippines - Alday, Rhea Mendoza (2007)
ABSTRACT This This study established the microbiology of shell stock and shucked oyster meats (n=30) vended in public markets (n=10) of the National Capital Region (NCR) of the Philippines. Handling practices of oyster retailers (n=24) and its vending environment were likewise documented and related to the microbiology of oysters. Microbiological analyses showed that retail Philippine oyster meats had total plate count ranging from 5.84 to 8.60 log10 CFU/g and from <4.71 to 8.77 log10 CFU/g, for shucked and shell stock oysters, respectively. Total Vibrio spp. population ranged from <2.36 to 5.03 log10 CFU/g for shucked oysters and from <2.00 to 5.99 log10 CFU/g for shell stocks. Total coliform counts ranged from <4.00 to 9.00 log10 CFU/g for shucked oysters and <3.93 to 11.00 log10 CFU/g for shellstocks, while generic Escherichia coli population ranged from <3.54 to 9.00 log10 CFU/g for shucked meats and <3.00 to 11.00 log10 CFU/g for shellstocks. Ninety seven percent of the total samples analyzed were found positive for presence of Salmonella spp. Most of these results exceeded the standard limits set by ICMSF and FDA. The overall microbial quality of shell stock and shucked oyster is significantly different between each other, with shucked oysters generally having higher microbial counts than shell stocks. Unsanitary vending and handling practices, unsatisfactory personal hygiene of retailers and unfavorable vending conditions could have contributed largely on the microbial load of shell stocks and shucked oysters.